Which technology diversification index should be selected? Insights for diversification perspectives - Keungoui Kim; Junseok Hwang; Sungdo Jung; Eungdo Kim (Cogent Business & Management, 2019)
The implacable list of diversification indices allows a wide range of selection opportunities for the researchers. The absence of consensus on the selection of suitable technology diversification index, however, may lead to a lack of objectivity with ample grounds. In this study, we focus on the case of technology diversification using patent to derive empirical implication for selecting suitable diversification index. To obtain the content validity of diversification index, three cases were tested: cross section, single and multiple time periods. As a result, diversification indices are separated into two groups: HHI, Gini-Simpson, 1/HHI, and Entropy for PC1 and Variety and Rao-Stirling for PC2. In this context, technology diversification can be explained by two perspectives of diversification: balance-centered and hetero-centered diversification. The balance-centered diversification implies the proportion of elements are the target of interest while hetero-centered diversification refers to variety and disparity of diversification, which focuses on the degree of differentiation among elements. In applicant-level technology diversification studies, these two diversification perspectives are recommended to be used. Subject classification codes: include these here if the journal requires them.
Keywords: 650; diversification index; technology diversification; patent; principal component analysis